Contractual Solidarity and Future Contractual Relations: A Comparative Legal Study - Abdulraoof, Sabah Erees; Al-Bsherawy, Ammar Kareim; Lafta, Naser Sabbr (CENTRAL ASIA AND THE CAUCASUS, 2022)
Contractual solidarity is a familiar title and traditionally seems to be a stable and stable system. Still, the meditator finds that it raises critical legal problems, whether it is the harmonization between it and the general rules of the contract or the obligation to cooperate information and security, as a point of balance between the conflicting interests of contractors. It leads to the emergence of personal rights that guarantee the legal protection of the contract, which allows the legislator and the judge to intervene to ensure the effectiveness of its judgments? How can each party to the contractual relationship satisfy the legitimate expectations of the other party without harming the other party? Which means that everyone owes the other and owes society under the idea of solidarity? The analytical study of this subject in this research is a serious attempt to answer these questions. The parties' selfish interests before the contract's conclusion cease and disappear upon the execution of the agreement, through the dependence of the parties on each other for their common interests, the so-called contractual solidarity. The idea of solidarity is not the result of the moment. Still, its emergence has extended to varying periods, and on this basis, this research will be divided into two topics that address the concept of contractual solidarity. In the second, we will explain how solidarity and contract are compatible.